Kehamilan remaja dan kejadian stunting pada anak usia 6-23 bulan di Lombok Barat - Irwansyah Irwansyah; Djauhar Ismail; Mohammad Hakimi (Berita Kedokteran Masyarakat (BKM), 2016)
Teenage pregnancy and the incidence of stunting in children aged 6-23 months in West LombokPurposeThis study aimed to analyze the risk of teenage pregnancy against stunting in children aged 6-23 months.MethodsThis study was an observational study with a matched case-control design. Control and case samples were each 55 samples, with a total sample of 110. The study subjects in the case group were children aged 6-23 months who suffered stunting. Children who did not suffer stunting were the control group. Samples were selected using two stage cluster random sampling. Analysis data used McNemar and conditional logistic regression tests with level of significance p <0.05 and confidence level (CI) 95%.ResultsThe finding of this study showed there was a significant association between teenage pregnancy and the incidence of stunting among children aged 6-23 months by controlling for the variables of maternal education, birth weight, and maternal stature (OR = 2.95; 95% CI: 1.05-8.26).ConclusionTeenage pregnancy, maternal short stature, low birth weight, and low maternal education were factors most likely contributed to increases in the incidence of stunting.